EDUCATIONAL MIGRATION IN THE MODERN RUSSIAN SOCIETY (ON THE EXAMPLE OF THE TOGLIATTI CITY) - Zhelnina, E.V; Payramova, I.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article raises the problems of the study of educational migration as a factor of social mobility: the main theoretical aspects of the analysis of social mobility, the approaches to the study of migration as a form of social mobility. The theoretical and methodological basis of the study is based on economic, sociological, demographic and psychological approaches. The article presents the results of the author's sociological research conducted in April 2019, aimed at studying the attitude of immigrant students of educational institutions of vocational education to educational migration. The study revealed that the majority of immigrant students come to the city of Togliatti from other settlements of the Samara region, Ulyanovsk region and the Republic of Tatarstan. The main reason for the move for most students was the admission to educational institutions of Togliatti on a budgetary basis. A significant part of the respondents showed a neutral attitude to the city of Togliatti. Most students do not regret moving to Togliatti, although they point out that they notice some shortcomings of the city. The main reasons for dislike for the city is its depression and poor environmental situation. There are more respondents who want to stay in the city among students receiving higher education. The vast majority of students do not feel like strangers in the city.